Effect of ecological factors in the distribution of Trifolium repens L. in Nepal - Shrestha, Anjali Maiya (Journal of Natural History Museum, 2008)
A detailed study on distribution of eight varieties of Trifolium repens L. (white clover) such as white flower and marked leaf (WML), white flower and non-marked leaf (WNML), white with pink tinged flower and marked leaf (WPML), white with pink tinged flower and non-marked leaf (WPNML), pink flower and marked leaf (PML), pink flower and non-marked leaf (PNML), light ping flower and marked leaf (LPML) and light pink flower and non-marked leaf (LPNML) from Nepal was carried out during the years 1994 through to 1997. Some ecological factors such as moisture, texture and pH of soil were found to be important parameters in the distribution of these varieties in different parts of Nepalese hills. Among these eight varieties, LPML and LPNML were not found in high altitude areas maybe due to unfavourable moisture, texture and pH conditions of soil. J. Nat. Hist. Mus. Vol.22, 2005 p.140-147